2010
DOI: 10.1108/17260531011086180
|View full text |Cite
|
Sign up to set email alerts
|

Cleaner production for environmental conscious manufacturing in the foundry industry

Abstract: PurposeThe purpose of the paper is to illustrate application of the cleaner production concept so as to incorporate environmental protection into business performance. The study analyses areas pertaining to the foundry industry that impact negatively on the environment leading to unsustainable resource utilisation and suggests options for promoting sustainable development within the industry, with specific focus on a foundry in a lower income country (LIC).Design/methodology/approachData were collected using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 19 publications
0
36
0
Order By: Relevance
“…Dhingra et al (2012) supposed that growing energy demand has led to increased global energy production with consequential increase in global warming emissions of CO 2 increased by 5.3% in 2010 to a record 30.4 giga tonnes; Netland and Aspelund (2014) reviewed the key dimensions to explain multi-plant improvement programme results in adopting, acting or avoiding of practices in subsidiaries; yielded the similarities between lean & green theoretical models to develop a comprehensive integrated model; Duarte and Cruz-Machado (2013) examined how diverse business models and frameworks can add value to modelling a lean and green approach; Huang et al (2009) examined the insights experienced in developing prototype solutions and the schemes for deploying smart objects in manufacturing to achieve real-time traceability & visibility while minimizing the total cost; Ghosh (2012) examined the current state of lean adoption in Indian manufacturing plants and its impact on operational performance; Ramirez et al (2014) identified the factors of environmentally-sustainable aids in firms' processes and charted the strategies to beat supplier barriers; Olhager and Parjago (2012) studied 216 Australian automotive firms and found clear difference of improvement initiatives between make-to-order & make-to-stock firms; Fore and Mbohwa (2010) illustrated the application of cleaner production in foundries in lower income country that impact negatively on the environment leading to unsustainable resource utilization, depletion and pollution; Miller et al (2010) presented a case study of RCELL projects to avoid over production or under production & unnecessary energy use; Anand and Kodali (2008) aimed at selecting lean as a strategy & preference ranking organization method for enrichment evaluations (PROMETHEE) to analyze its impact on stakeholders, through case studies in SMEs.…”
Section: Grouping 3: Theoretical Concernsmentioning
confidence: 99%
“…Dhingra et al (2012) supposed that growing energy demand has led to increased global energy production with consequential increase in global warming emissions of CO 2 increased by 5.3% in 2010 to a record 30.4 giga tonnes; Netland and Aspelund (2014) reviewed the key dimensions to explain multi-plant improvement programme results in adopting, acting or avoiding of practices in subsidiaries; yielded the similarities between lean & green theoretical models to develop a comprehensive integrated model; Duarte and Cruz-Machado (2013) examined how diverse business models and frameworks can add value to modelling a lean and green approach; Huang et al (2009) examined the insights experienced in developing prototype solutions and the schemes for deploying smart objects in manufacturing to achieve real-time traceability & visibility while minimizing the total cost; Ghosh (2012) examined the current state of lean adoption in Indian manufacturing plants and its impact on operational performance; Ramirez et al (2014) identified the factors of environmentally-sustainable aids in firms' processes and charted the strategies to beat supplier barriers; Olhager and Parjago (2012) studied 216 Australian automotive firms and found clear difference of improvement initiatives between make-to-order & make-to-stock firms; Fore and Mbohwa (2010) illustrated the application of cleaner production in foundries in lower income country that impact negatively on the environment leading to unsustainable resource utilization, depletion and pollution; Miller et al (2010) presented a case study of RCELL projects to avoid over production or under production & unnecessary energy use; Anand and Kodali (2008) aimed at selecting lean as a strategy & preference ranking organization method for enrichment evaluations (PROMETHEE) to analyze its impact on stakeholders, through case studies in SMEs.…”
Section: Grouping 3: Theoretical Concernsmentioning
confidence: 99%
“…Being the source of wealth generation, foundries had been started in many countries in the olden days. After the middle part of the twentieth century, the requirement of cast components increased to a large volume in the world (Fore and Mbohwa, 2010). As a result, foundries amazingly increased in number in several countries.…”
Section: Resultsmentioning
confidence: 99%
“…On the whole the research reported by these authors have revealed that, choosing appropriate devices to control the emissions of pollutants from aluminum pressure die casting plants has to be done meticulously so that the cleaner production principles are implemented economically in them. Fore and Mbohwa (2010) have extensively reviewed the application of cleaner production technology in foundries located in various countries in the world. While the major emphasis of these authors is that, the application of cleaner production technology will result in energy saving in foundries, the information furnished by them on the significance of applying cleaner production technologies in foundries is highly noteworthy.…”
Section: Cleaner Production In Foundries Through Pollution Control Dementioning
confidence: 99%
See 1 more Smart Citation
“…An important inference drawn frame this research is that no single device or approach will reduce the emission of pollutants from the aluminum pressure die casting plants. Fore and Mbohwa (2010) have given suggestions to reduce the pollutants by the foundries. These authors have traced various aspects of controlling pollution from foundry units.…”
Section: Centrifugal Collectorsmentioning
confidence: 99%